Adaptive Façade Strategies for Energy Efficiency: A Case Study Optimization in Cold and Semi-Arid Climates - Gholami, Hanieh; Rezaei, Fatemeh; M. Ahmadi, Hanieh (International Journal of Architectural Engineering Technology, 2025)
The increasing global energy consumption in the building sector highlights an urgent need for energy-efficient design solutions. This study investigates the optimization of residential building envelopes in Bojnord, Iran—a city with a cold and semi-arid climate (BSk), characterized by harsh winters and relatively warm summers. A simulation-based methodology was adopted using parametric modeling and building energy simulation tools to assess envelope performance. Five façade strategies were selected for evaluation based on their climatic relevance, geometric adaptability, and feasibility within common construction limitations: optimized Window-to-Wall Ratio (WWR), ventilated double-skin façades (DSF) with air insulation and shading, Voronoi-based shading systems, perforated panels, and variable-porosity façades inspired by traditional Iranian geometry. Adaptive versions of these strategies were also examined. Results indicate that optimizing the WWR to 20% significantly reduces energy consumption, while dynamic façade systems—particularly those with adjustable WWR—offer the highest energy savings, reducing total consumption by approximately 7.73% compared to the baseline model. Conversely, some fixed strategies such as static perforated façades led to increased energy use. The findings provide insights for architects and urban planners into the role of adaptive and climate-responsive envelope systems in achieving energy efficiency and thermal comfort in cold and semi-arid regions. Limitations related to material costs, control complexity, and long-term performance of dynamic systems are also discussed.